BUNGA MAWAR SEBAGAI SIMBOL WANITA DALAM KARYA SENI LUKIS - HARLIANA, Drs. Erfahmi,M.Sn, Drs. Yusron Wikarya, M. Pd (Serupa The Journal of Art Education, 2014)
The purpose of this thesis is to visualize the rose as a symbol of women in the works of surrealist art with the flow, so that people are more responsive to women's behavior that exist at the present time. The method of painting creation through small sketches on paper and translated into media canvas with objects displays of roses, with staining technique that accentuates the colors monochromatic, as well as the creator's imagination combines with the elements and principles of art so produced ten paintings by surrealist stream, with the title: (1) Rose Thorns, (2) your Eye Ball, (3) Women's Tough, (4) Hurt, (5) Load, (6) Thy Shadow, (7) Blooming, (8) Caught, (9) Confined, (10) Unrestricted.keyword: Roses, Symbol, Women, Art, Surrealists